KEBIJAKAN HUKUM PIDANA DALAM PENANGGULANGAN TINDAK PIDANA ABORTUS PROVOKATUS - Halimatusaddiah Siregar; Bagus Ramadi (Causa: Jurnal Hukum dan Kewarganegaraan, 2023)
This research aims to investigate how criminal policies that deal with abortions that are provoked are reviewed in relation to provokatus acts of abortion. criminal and sanctions given to the perpetrators of abortion provocatus criminal acts. In examining this problem using normative juridical research methods, it can be concluded that the criminal act of provocative abortion is prohibited and threatened with criminal sanctions, regardless of the context in which the act is committed and who does it, namely anyone, both the perpetrator and the perpetrator (abortion facilitator). Regulated in the Criminal Code Act articles 346, 347, 349 of the Criminal Code which describes the criminal penalties for the crime of provocative abortion, but in this case there are still exceptions regulated in Article 75 Paragraph 2 of Health Law Number 36 of 2009 which allows abortion.